2022
DOI: 10.26434/chemrxiv-2022-30zcn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wild Type and Omicron SARS-CoV-2 Spike Receptor Binding Domains Bind Similarly to the Human ACE2 Receptor: An MM-GBSA Study

Abstract: SARS-CoV-2 is a coronavirus that has created a global pandemic. The virus contains a spike protein which has been shown to bind to the ACE2 receptor on the surface of human cells. Vaccines have been developed that recognize elements of the SARS-CoV-2 spike protein and they have been successful in preventing infection. Recently, the omicron variant of the SARS-CoV-2 virus was reported and quickly became a variant of concern due to its transmissibility. This variant contained an unusually large number (32) of po… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Of the mutually detected mutations in the 3 Omicron subvariants, a previous study showed that Q493R and N501Y, along with S477N, formed a new interaction with human ACE2, which enhanced the binding of the Omicron variant to human ACE2 [ 16 ]. The Y505H mutation did not seem to have an impact on binding [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the mutually detected mutations in the 3 Omicron subvariants, a previous study showed that Q493R and N501Y, along with S477N, formed a new interaction with human ACE2, which enhanced the binding of the Omicron variant to human ACE2 [ 16 ]. The Y505H mutation did not seem to have an impact on binding [ 17 ].…”
Section: Discussionmentioning
confidence: 99%